Redemption of the Damned, Vol. 1: Aerial Phenomena by Martin Shouth with Wim van Utrecht - Clark, Jerome (Journal of Scientific Exploration, 2019)
Reading Charles Fort at an early age did my subsequent career and income no favor, but it did make my life more interesting. My admiration for Fort's cheeky attitude toward received wisdom has only expanded with time. I will always be, first and foremost, a Fortean. The omnibus Books of Charles Fort (1941) was what I read after consuming Edward Ruppelt's The Report on Unidentified Flying Objects (1956). So I signed up as a ufologist; Fort, after all, was the first of the species. In The Book of the Damned (1919) he argued for the reality of interplanetary visitation, his serious purpose only thinly masked in jokey prose. In the summer of 1947, when flying saucers became an inescapable presence, it was Forteans who alerted otherwise clueless journalists to the long history of intriguing aerial phenomena, thus introducing what would be called the extraterrestrial hypothesis (ETH) into popular culture and subsequent discourse. On the occasion of Damned's first century, Scottish UFO scholar Martin Shough, assisted by Belgian colleague Wim van Utrecht, offers up a kind of revisionist answer to Fort. Redemption of the Damned, Vol. 1: Aerial Phenomena uses the Internet and other tools to examine Fort's sources and to analyze how they look through the lens of current scientific knowledge. Fort helpfully provided future anomalies chroniclers with source citations that let us know where his data came from. Overwhelmingly, it was period journals and newspapers. Shough with Utrecht finds his way to those and reconsiders the cases, at considerably greater length, which Fort typically summarized, often with accompanying wisecracks, in no more than brief sentences andparagraphs.